1995
DOI: 10.1128/iai.63.5.2021-2025.1995
|View full text |Cite
|
Sign up to set email alerts
|

Local and systemic antibody responses to dextran-cholera toxin B subunit conjugates

Abstract: This study was designed to test local and systemic immunity following mucosal immunization with a polysaccharide-protein conjugate. After preparing and characterizing dextran-cholera toxin B subunit (CTB) conjugates, we studied their immunogenicity in mice following systemic or mucosal immunizations. Dextran was chosen as a model polysaccharide antigen and conjugated via adipic acid dihydrazide and N-succinimidyl-3-(2-pyridyldithio)propionate to CTB. Mice were immunized either subcutaneously, intranasally, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 40 publications
2
33
0
Order By: Relevance
“…We and others have previously shown that mice intranasally immunized with proteins mixed with LT or cholera toxin B not only produce a systemic IgG response but also antibody responses at different mucosal sites 7,9–12,16–19 . As has been shown for model immunogens such as ovalbumin, the C‐fragment of TT 11,12 and herpes simplex virus type 2 glycoprotein, 19 mice immunized intranasally with hCG mixed with LT will produce antigen‐specific IgG in the serum as well as sIgA in both the respiratory and genital tracts.…”
Section: Discussionmentioning
confidence: 83%
“…We and others have previously shown that mice intranasally immunized with proteins mixed with LT or cholera toxin B not only produce a systemic IgG response but also antibody responses at different mucosal sites 7,9–12,16–19 . As has been shown for model immunogens such as ovalbumin, the C‐fragment of TT 11,12 and herpes simplex virus type 2 glycoprotein, 19 mice immunized intranasally with hCG mixed with LT will produce antigen‐specific IgG in the serum as well as sIgA in both the respiratory and genital tracts.…”
Section: Discussionmentioning
confidence: 83%
“…It is therefore important to define the optimal routes, and to identify suitable delivery systems and adjuvants for inducing local immunity. We have used CT and its B subunit, CTB, since these molecules have been proved to be good mucosal immunogens and carriers for other antigens (4,23,(29)(30)(31)33). The toxicity of CT precludes its exploitation in human vaccines, whereas CTB is non-toxic as tested by different routes in humans (1 1, 18, 34).…”
Section: Discussionmentioning
confidence: 99%
“…This may partly be due to their lack of uptake by mucosal tissues (16). Cholera toxin (CT) and the heatlabile enterotoxin from Escherichia coli (LT) are exceptionally potent mucosa-binding molecules and have been shown to induce strong immune responses after mucosal immunization (4,17,(18)(19)(20)(21). These molecules bind with high affinity to mucosal (and other) cells (18) and they have been used as mucosal adjuvants and carriers for non-binding protein, peptide and polysaccharide antigens (4,(19)(20)(21).…”
mentioning
confidence: 99%
“…Two to five mice from each group were killed, and the lungs or upper respiratory tracts were removed. Secretory antibodies were extracted as described by Bergquist et al [16]. Briefly, the mice were injected intraperitoneally with 0·1 ml 1% heparin-PBS under anaesthesia.…”
Section: Collection Of Samplesmentioning
confidence: 99%